2006
DOI: 10.1016/j.phytochem.2006.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate (EGCG): Chemical and biomedical perspectives

Abstract: The compound (-)-epigallocatechin-3-gallate (EGCG) is the major catechin found in green tea [Camellia sinensis L. Ktze. (Theaceae)]. This polyphenolic compound and several related catechins are believed to be responsible for the health benefits associated with the consumption of green tea. The potential health benefits ascribed to green tea and EGCG include antioxidant effects, cancer chemoprevention, improving cardiovascular health, enhancing weight loss, protecting the skin from the damage caused by ionizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
318
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(330 citation statements)
references
References 25 publications
3
318
0
9
Order By: Relevance
“…As principais catequinas do chá são (-) epigalocatequina galato (EGCG), (-) epigalocatequina (EGC), (-) epicatequina galato (ECG), epicatequina (EC) e catequina (C). A catequina mais abundante e ativa do chá verde é a EGCG (NAGLE; FERREIRA; ZHOU, 2006;PROVAN;. Além das catequinas, quantidades apreciáveis de flavonoides como quercetina e miricetina e seus glicosídeos estão presentes no chá verde (SAITO; MIYATA, 2000.…”
Section: Determinação Dos Sólidos Solúveisunclassified
“…As principais catequinas do chá são (-) epigalocatequina galato (EGCG), (-) epigalocatequina (EGC), (-) epicatequina galato (ECG), epicatequina (EC) e catequina (C). A catequina mais abundante e ativa do chá verde é a EGCG (NAGLE; FERREIRA; ZHOU, 2006;PROVAN;. Além das catequinas, quantidades apreciáveis de flavonoides como quercetina e miricetina e seus glicosídeos estão presentes no chá verde (SAITO; MIYATA, 2000.…”
Section: Determinação Dos Sólidos Solúveisunclassified
“…The main substances found in green tea are caffeine (2-4%), amino acids (4%), lignin (6.5%), organic acids (1.5%), protein (15%), chlorophyll (0.5%), and the polyphenols (25-35%). 4 The beneficial effects of green tea are attributed to the polyphenolic compounds present that are essentially colorless. Epigallocatechin gallate (EGCG) and epigallocatechin (EGC) are the most important polyphenols (Figure 2), and a cup of green tea contains about 300-400 mg of polyphenols or 10-30 mg of EGCG.…”
Section: Discovery Of the Medicinal Properties Of Teasmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG) and epigallocatechin (EGC) are the most important polyphenols (Figure 2), and a cup of green tea contains about 300-400 mg of polyphenols or 10-30 mg of EGCG. 4 Because of the differences in the processing of tea leaves after harvest, catechins are present in higher quantities in green tea than in black or oolong tea.…”
Section: Discovery Of the Medicinal Properties Of Teasmentioning
confidence: 99%
“…Epidemiological evidence and several randomized controlled intervention trials have shown an inverse relationship between habitual tea consumption (predominately green tea) and levels of body fat and waist circumference [64], [65]. While green tea contains an array of compounds, the putative antiobesity effects have been most commonly attributed to the polyphenolic fraction of green tea, specifically the catechins [66].Green tea catechins induces antiobesity effects by thermogenesis and substrate oxidation which are mediated by sympathetic nervous system activity, modifications in appetite control, down-regulation of enzymes involved in hepatic lipid metabolism, and decreased nutrient absorption [63]. But according to Pan etal., [67]black tea polyphenols are more effective than green tea polyphenols in body weight reduction.…”
Section: Bone Mineral Densitymentioning
confidence: 99%